2007
DOI: 10.1007/s10815-007-9110-4
|View full text |Cite
|
Sign up to set email alerts
|

The impact of the depth of embryo replacement on IVF outcome

Abstract: Purpose: To evaluate the effect of the depth of embryo transfer replacement on clinical pregnancy rate.Methods: Data from a total of 104 consecutive embryo transfers performed on 104 womenn aged 26-37 years were prospectively collected for this study. All patients underwent a standard down regulation protocol for ovarian stimulation. Oocytes retrieval were performed at 36 h after hCG administration. Embryo transfer took place at 48 h after insemination. The patients were matched in two groups according to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
33
1
5

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 29 publications
2
33
1
5
Order By: Relevance
“…Studies have used various ultrasonographic parameters at the time of transfer to assess optimal transfer technique. Investigators measuring the distance from the catheter tip to the fundus have found higher pregnancy rate (PR) overall when the catheter tip was further away from the fundus (1,2), with some suggesting that the odds of clinical pregnancy increase by 11% for every additional millimeter the catheter tip is placed further from the fundus (3).…”
mentioning
confidence: 99%
“…Studies have used various ultrasonographic parameters at the time of transfer to assess optimal transfer technique. Investigators measuring the distance from the catheter tip to the fundus have found higher pregnancy rate (PR) overall when the catheter tip was further away from the fundus (1,2), with some suggesting that the odds of clinical pregnancy increase by 11% for every additional millimeter the catheter tip is placed further from the fundus (3).…”
mentioning
confidence: 99%
“…No difference in ectopic pregnancy rates was observed with different distances of embryo deposition from the uterine fundus (10-15 mm or < 10 mm) (Pacchiarotti et al, 2007).…”
Section: Air Bubble Position After Embryo Transfermentioning
confidence: 86%
“…7 The patients were matched in two groups according to the distance between the tip of the catheter and the uterine fundus at transfer (group A >10 and <15 mm; group B <10 mm). Clinical PRs varied significantly between the two groups and it was 27.7% in group A and 14% in group B (P<.05).…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6][7] The common end-result achieved by these studies was that embryo transfer at or within 10 mm of the fundal endometrial surface was associated with a lower pregnancy rate (PR) compared with embryo transfer >10 mm below the fundal endometrial surface. [5][6][7] In the present study, we measured by trans-vaginal ultrasound the distance from the air bubble injected with the embryos and the fundal endometrial surface (EFD) in order to assess if EFD affects pregnancy and implantation rates.…”
Section: Introductionmentioning
confidence: 99%